Benchmarking Nonlinear Controllers for a Quad Active Bridge Resonant Converter Supplying Pulsed Power Loads in DC Microgrids - Nduwamungu, Aphrodis; Lie, Tek Tjing; Nair, Nirmal KC; Lestas, Ionis (Elsevier BV, 2026)
This paper investigates advanced nonlinear control strategies for a Quad Active Bridge (QAB) resonant converter supplying pulsed power loads (PPLs) in DC microgrids, where fast load transients and inter-port coupling challenge voltage stability. Three controllers are designed and evaluated for regulating the 48 V ports 3 and 4 under a PPL step from 100 W to 200 W : ASSOSMC, IHOSMC, and CMPC–ISMC. In terms of voltage regulation, ASSOSMC achieves the smallest peak deviations ( Δ V 3 = 0 . 5 V , Δ V 4 = 0 . 3 V ), whereas IHOSMC and CMPC–ISMC exhibit larger voltage dips of 3 . 0 / 2 . 8 V and 3 . 5 / 4 . 2 V at ports 3/4, respectively. Overshoot is kept below 1.531% (ASSOSMC) and limited to 0.667% (IHOSMC and CMPC–ISMC), with fast settling times of 3 . 6 μ s (ASSOSMC and CMPC–ISMC) and 4 . 7 μ s (IHOSMC). Energy efficiency is evaluated from steady-state averaged port powers over a common interval ( t = 2 . 1166 – 2 . 8610 s ): CMPC–ISMC achieves the highest overall efficiency ( η tot ≈ 90 . 775 % ), followed by ASSOSMC ( η tot ≈ 90 . 724 % ) and IHOSMC ( η tot ≈ 89 . 055 % ). Hardware-in-the-loop validation on an OPAL-RT platform confirms the effectiveness of the proposed controllers for stabilizing QAB port voltages under PPL disturbances, and highlights CMPC–ISMC as a balanced solution combining high efficiency with reduced current stress on the regulated ports.
Keywords: 40 Engineering; 4008 Electrical Engineering; 4009 Electronics, Sensors and Digital Hardware; 7 Affordable and Clean Energy; Integral HOSM; Model predictive control with ISMC; ASSOSMC; OPAL-RT